2021
DOI: 10.1002/cam4.4472
|View full text |Cite
|
Sign up to set email alerts
|

Association of PTPRT mutations with immune checkpoint inhibitors response and outcome in melanoma and non‐small cell lung cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 71 publications
(133 reference statements)
1
26
2
Order By: Relevance
“…Of them, AR has been demonstrated to negatively regulate PD-L1 expression, and therefore lower AR-expressed tumors achieved a better response to immunotherapy in hepatocellular carcinoma ( Jiang et al, 2020 ). In addition, patients with PTPRT mutations harbored favorable ORR and survival outcomes in several tumor types ( Zhang et al, 2022 ). However, the associations of other genes used in our model with ICI efficacy have not been reported, although some of them have been found to play critical roles in cancer, such as COL5A2 ( Han et al, 2022 ), FAT2 ( Gao et al, 2014 ), ITPR3 ( Wu et al, 2021 ), PCDH20 ( Wang et al, 2016 ), and UTRN ( Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of them, AR has been demonstrated to negatively regulate PD-L1 expression, and therefore lower AR-expressed tumors achieved a better response to immunotherapy in hepatocellular carcinoma ( Jiang et al, 2020 ). In addition, patients with PTPRT mutations harbored favorable ORR and survival outcomes in several tumor types ( Zhang et al, 2022 ). However, the associations of other genes used in our model with ICI efficacy have not been reported, although some of them have been found to play critical roles in cancer, such as COL5A2 ( Han et al, 2022 ), FAT2 ( Gao et al, 2014 ), ITPR3 ( Wu et al, 2021 ), PCDH20 ( Wang et al, 2016 ), and UTRN ( Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that PTPRT mutation is positively correlated with TMB, and patients with PTPRT mutation might benefit from ICI therapy, indicating that PTPRT is a potential biomarker in immunotherapy [ 8 , 9 ]. Based on the prediction based on recurrent mutations in PTPRT , we identified potential PTPRT neoantigens ( Table 2 ) that might have a therapeutic value in immunotherapies, for example, cancer vaccines or T cell therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The gene may be involved in both signal transduction and cellular adhesion and is also known to inhibit malignant cell proliferation by inhibiting the STAT3 pathway [ 4 7 ]. Recent studies have reported that PTPRT mutations may be associated with the tumor mutation burden (TMB) and could provide clinically predictive implications for immune checkpoint inhibitor (ICI) therapies [ 8 , 9 ]. Hu et al reported that PTPRT may be involved in the early metastatic seeding of colorectal cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have revealed the potential implications of TMB for evaluating cancer immunotherapeutic efficacy [ 8 , 12 , 13 , 53 ]. However, in clinical practice, the determination of TMB needs to conduct whole-exome mutational detection [ 54 ]. Another disadvantage of the TMB application is the uncertain cut-off values in distinct cancer types [ 54 ].…”
Section: Discussionmentioning
confidence: 99%